#TITLE_ALTERNATIVE# - WILIARDY (NIM : 10211030), ABEDNEGO
...... Taking several assumption, such as 1) the ambient manifold M to be maximally symmetric space and satisfying a pure gauge condition, and 2) the submanifold is taken to be at (Rn), we find then the solution W that satisfies Ricci scalar of N. Moreover, we will find the compatibility of the solution with the Ricci and Riemann tensor of manifold N depending on the dimension n.